An Oxidative Enzyme Boosting Mechanical and Optical Performance of Densified Wood Films. Issue 17 (26th January 2023) - Koskela, Salla; Wang, Shennan; Li, Lengwan; Zha, Li; Berglund, Lars A.; Zhou, Qi
Abstract: Nature has evolved elegant ways to alter the wood cell wall structure through carbohydrate‐active enzymes, offering environmentally friendly solutions to tailor the microstructure of wood for high‐performance materials. In this work, the cell wall structure of delignified wood is modified under mild reaction conditions using an oxidative enzyme, lytic polysaccharide monooxygenase (LPMO). LPMO oxidation results in nanofibrillation of cellulose microfibril bundles inside the wood cell wall, allowing densification of delignified wood under ambient conditions and low pressure into transparent anisotropic films. The enzymatic nanofibrillation facilitates microfibril fusion and enhances the adhesion between the adjacent wood fiber cells during densification process, thereby significantly improving the mechanical performance of the films in both longitudinal and transverse directions. These results improve the understanding of LPMO‐induced microstructural changes in wood and offer an environmentally friendly alternative for harsh chemical treatments and energy‐intensive densification processes thus representing a significant advance in sustainable production of high‐performance wood‐derived materials. Abstract : Lytic polysaccharide monooxygenase (LPMO) is a cellulose‐oxidizing enzyme that has applications in production of renewable materials and biofuels. Here, LPMO is discovered to nanofibrillate the cellulose microfibril bundles in situ inside wood cell wall. Thus, LPMO‐treated delignified wood becomes susceptible to densification at low pressure and room temperature, enabling environmentally friendly production of transparent anisotropic films with ultrahigh tensile strength.